The effect of ameliorants on improvement of soil fertility in post gold mining land at West Kalimantan - Sulakhudin Mastur; Denah Suswati; Muhammad Hatta (Brawijaya University, 2017)
The application of ameliorant has been suggested to improve soil fertility and crop growth in post illegal gold mining (PIGM) lands. This study evaluated the effect of ameliorant types and semi-permeable layer on properties of soil in PIGM lands and growth of sorghum. A field experiment employed two treatments, i.e. type of ameliorant and semi-permeable layer. There were four ameliorant types applied i.e., without ameliorant (M0); coastal sediment at a dose of 40 t/ha (M1); biochar at a dose of 4 t/ha (M2), and coastal sediment at a dose of 30 t/ha + 4 t biochar/ha(M3). The second treatment consisted of two levels, namely: without a semi-permeable layer (S0) and the semi-permeable layer of 20 cm depth from the soil surface (S1). The results showed that types of ameliorant gave different effect to soil properties. Application of coastal sediment at a dose of 40 t/ha significantly increased the contents of Ca and Mg, whereas application of biochar at a doses of 4 t/ha increased soil CEC. The semi-permeable layer did not significantly affect plant height and stem diameter of sorghum. The highest of sorghum growth was reached by application of coastal sediment at a dose of 30 t/h + biochar at a dose of 4 t/ha. The combination of coastal sediment and biochar from banana peels could complement each other to improve soil fertility in PIGM land